Modern biotelemetric system architecture for use by patients and physicians - Krejcar, Ondrej; Fojcik, Petr (Lékař a technika, 2008)
Need of existence of soft ware platform, which will allow us to monitor the patients bio-parameters and provide us with services which help with full health care, is more than relevant these days. Increasing amount of information, a new trend in home health care or desire of individuals to increase their life quality are only some aspects which confi rm this need. Project Guardian concerns with this problem. Its aim is to provide solution which can be used in diff erent spheres of health care and which will be available through PDA, web or desktop clients. Because of that the Guardian platform is based on client-server model where the web service presents server and communicates directly with database. Clients are represented by applications which use services of web service. Applying of web services provide large extension of Guardian to diff erent spheres so Guardian is not limited only for existing clients which are indispensable part of platform, but allow us the implementation of the third parties clients.
Keywords: financování organizované; telemetrie; Signal Processing, Computer-Assisted; Telemedicine; počítačové zpracování signálu; Computer Communication Networks; Monitoring, Ambulatory; lidé; Computers, Handheld; telemedicína; urgentní lékařství; Electronic Data Processing; automatizované zpracování dat; Financing, Organized; počítače do ruky; Telemetry; Internet; ambulantní monitorování; Emergency Medicine; počítačové komunikační sítě; internet; Humans